2008
DOI: 10.1091/mbc.e07-07-0728
|View full text |Cite
|
Sign up to set email alerts
|

Cleavage of Stalled Forks by Fission Yeast Mus81/Eme1 in Absence of DNA Replication Checkpoint

Abstract: During replication arrest, the DNA replication checkpoint plays a crucial role in the stabilization of the replisome at stalled forks, thus preventing the collapse of active forks and the formation of aberrant DNA structures. How this checkpoint acts to preserve the integrity of replication structures at stalled fork is poorly understood. In Schizosaccharomyces pombe, the DNA replication checkpoint kinase Cds1 negatively regulates the structure-specific endonuclease Mus81/Eme1 to preserve genomic integrity whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
71
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(83 citation statements)
references
References 61 publications
(80 reference statements)
10
71
0
1
Order By: Relevance
“…Although it is not clearly essential for fork collapse in all cell types, the Mus81-Eme1 complex in Schizosaccharomyces pombe plays a crucial role in DSB generation at stalled replication forks (Froget et al 2008), and a similar relationship has been observed in mammalian cells when CHK1 is inhibited (Forment et al 2011). These findings in aggregate suggest that PLK1 could play an active facilitative role in replication fork collapse at the level of both the replisome and cleaving aberrant fork structures.…”
mentioning
confidence: 72%
See 1 more Smart Citation
“…Although it is not clearly essential for fork collapse in all cell types, the Mus81-Eme1 complex in Schizosaccharomyces pombe plays a crucial role in DSB generation at stalled replication forks (Froget et al 2008), and a similar relationship has been observed in mammalian cells when CHK1 is inhibited (Forment et al 2011). These findings in aggregate suggest that PLK1 could play an active facilitative role in replication fork collapse at the level of both the replisome and cleaving aberrant fork structures.…”
mentioning
confidence: 72%
“…The SLX4-endonuclease complex has previously been implicated as a mediator of replication fork collapse, particularly in cooperation with the MUS81-EME1 complex (Froget et al 2008;Forment et al 2011;Matos et al 2011;Gallo-Fernandez et al 2012;Munoz-Galvan et al 2012;Schwartz et al 2012;Szakal and Branzei 2013). To examine the involvement of this complex in the DSBs generated upon fork stalling in ATR-deficient cells, Crelox conditional SLX4 cells were used to delete Slx4 and determine the effect of its absence on DSB generation following ATR inhibition and fork stalling.…”
Section: Rnf4 and Plk1 Are Required For Slx4-dependent Dsb Formation mentioning
confidence: 99%
“…This is accompanied by DNA doublestrand breaks (DSBs), histone H2A phosphorylation (phospho-H2A; H2Ax in metazoans), and accumulation of the Rad52 recombination protein in repair foci (1,30). These markers are a feature of replication fork collapse (5,14,27), which results in Chk1 kinase activation (26). Because the G 2 -M damage checkpoint is activated, cells do not divide prematurely (8,26,55).…”
mentioning
confidence: 99%
“…Although CHK1 may play different roles than WEE1 in this process (45), further studies may address whether nucleotide shortage contributes to replication stalling and DNA damage following CHK1 inhibition of reoxygenated cells. Importantly, stalled forks can act as substrates for endonucleases (46), which may cause excessive DNA damage if not controlled properly, and CHK1 may directly or indirectly be involved in suppression of such endonucleases (33,47,48).…”
Section: Discussionmentioning
confidence: 99%